PENGARUH JUMLAH PENDUDUK, JUMLAH WAJIB PAJAK DAN INFLASI TERHADAP TUNGGAKAN PAJAK DI SULAWESI SELATAN - M, Nurwani (Economos : Jurnal Ekonomi dan Bisnis, 2018)
The purpose of this studi  was to examine the influence or economic growth, number of tax payers againts and inflation rate the tax arrears in South Sulawesi either simultaneously or partially. The research used secondary data where from respondents and sekuder obtained from BPS South Sulawesi, and other journal.  The secondary data where the influence or economic growth, number of tax payers againts and inflation rate and the tax arrears, related to the number of registered corporate taxpayers. where used double linear regresion by using software SPSS version 16.0 for windows aplications. Simultaneous hypothesis testing results show that simultaneous system Effects of the influence or economic growth, number of tax payers againts and inflation rate the tax arrears in South Sulawesi. The results and partial hypothesis can be seen that economic growth (X1) affect tax arrears, it is shown to influence the direction of the positiftive and significant.  while the inflation rate (X2) no effect amound of tax arrears and Number of tax payers againts (X3) significant negative amound of tax arrears in South Sulawesi.